Single High-Dose Vitamin D Supplementation as an Approach for Reducing Ultramarathon-Induced Inflammation: A Double-Blind Randomized Controlled Trial - Mieszkowski, Jan; Borkowska, Andżelika; Stankiewicz, Błażej; Kochanowicz, Andrzej; Niespodziński, Bartłomiej; Surmiak, Marcin; Waldziński, Tomasz; Rola, Rafał; Petr, Miroslav; Antosiewicz, Jędrzej (Nutrients, 2021)
Purpose: A growing number of studies indicate the importance of vitamin D supplementation for sports performance. However, the effects of a single high-dose vitamin D supplementation on ultramarathon-induced inflammation have not been investigated. We here analyzed the effect of a single high-dose vitamin D supplementation on the inflammatory marker levels in ultramarathon runners after an ultramarathon run (maximal run 240 km). Methods: In the study, 35 runners (amateurs) were assigned into two groups: single high-dose vitamin D supplementation group, administered vitamin D (150,000 IU) in vegetable oil 24 h before the start of the run (n = 16); and placebo group (n = 19). Blood was collected for analysis 24 h before, immediately after, and 24 h after the run. Results: Serum 25(OH)D levels were significantly increased after the ultramarathon in both groups. The increase was greater in the vitamin D group than in the control group. Based on post-hoc and other analyses, the increase in interleukin 6 and 10, and resistin levels immediately after the run was significantly higher in runners in the control group than that in those in the supplementation group. Leptin, oncostatin M, and metalloproteinase tissue inhibitor levels were significantly decreased in both groups after the run, regardless of the supplementation. Conclusions: Ultramarathon significantly increases the serum 25(OH)D levels. Attenuation of changes in interleukin levels upon vitamin D supplementation confirmed that vitamin D has anti-inflammatory effect on exercise-induced inflammation.
Keywords: sportovní výkon; ultramarathon; Humans; lidé středního věku; Double-Blind Method; Adaptation, Physiological; inflammation; dospělí; Inflammation; dvojitá slepá metoda; lidé; Biomarkers; IL-6; Vitamin D; zánět; resistin; Adult; biologické markery; Male; Middle Aged; potravní doplňky; maratonský běh; Dietary Supplements; fyziologická adaptace; Athletic Performance; Marathon Running; mužské pohlaví; vitamin D; skeletal muscle damage